Performance evaluation of improved mung bean (Vigna radiata (L.) Wilczek) varieties at low moisture areas East Shewa, Oromia, Ethiopia - Dinsa, Temesgen; Balcha, Urgaya; Benya, Fayisa; Fufa, Mihratu (Journal of Scientific Agriculture, 2022)
Mung bean is a useful crop in drier areas and has a good potential for crop rotation and relay cropping with cereals using residual moisture. The experiment was conducted at Adami Tulu Agricultural Research Center (ATARC), Lume and Dugda during 2018 and 2019 with the objective to identify adaptable and high yielder mung bean varieties for East Shewa Zone and similar agro ecologies. Four released mung bean varieties Shewa robit, Beroda, N-26 and Arkebe used as planting material. The experiment was laid down in Randomized Complete Block Design (RCBD) with three replications. The plot size was 1.8m × 2.5 m (4.5 m2) having 6 rows and a spacing of 0.30 m between rows and 50 cm between replication, 1 m between blocks. Data’s like height (cm), number of pods per plant, number of seeds per pod, days to days to flowering, days to maturity, grain yield (kg ha-1), 100 seed weight (g) were collected and analyzed using SAS software. The combined analysis of variance showed that there was significant variation at (P≤0.05 and P≤0.01) among the studied varieties, locations, and year main effect. There were also significant interaction effect on location by year, varieties by year and location by varieties by year for grain yield and other yield components. But non-significant on varieties by location for all traits except plant height and indicated those varieties were performed similarly across the locations. Shewa Robit variety had a higher grain yield (1607.4 kg ha-1) followed by N-26 (1542 kg ha-1) and Beroda (1466.1 kg ha-1). While Arkebe Variety had a lower grain yield (893.4 kg ha-1) as compared with other varieties. Therefore Shewa Robit and N-26 were recommended for the study area and similar agro-ecologies.